Identifying the health and well-being benefits of recreational fishing. - McManus, Alexandra; Newton, Wendy; Storey, Jessica; White, James (Centre of Excellence Sceicne Seafood & Health (CESSH) Curtin University, 2011)
In summary, this study found that considerable health and well-being benefits can be gained through involvement in recreational fishing. Encouraging young children, youth, adults and families to fish offers a cost effective and healthful outdoor recreational activity that can be enjoyed throughout life. Benefits were evident for individuals and groups. Recreational fishing was also noted to provide significant benefits to children and youth with behavioural and mental health issues. Finally, educational strategies that focus on how to minimise the environmental impacts of recreational fishing can ensure today’s and tomorrow’s recreational fishers are aware of sustainable fishing practices.